From Selection to Influence: The Moderating Role of Classroom Norms in the Evolution of Aggression and Victimization in Adolescent Friendship Networks. - Guo, Ruonan; Hou, Ke; Li, Tian; Li, Caina (Journal of Youth & Adolescence, 2025)
Aggression and victimization are well-documented factors influencing adolescent social relationships, yet little is known about how these behaviors interact with friendship networks, particularly in the context of aggression norms. This study explored the relationships between aggression, victimization, and friendship networks, and further examined the moderating role of two types of aggression norms among Chinese adolescents using longitudinal social network analysis. A sample of 879 students (M = 12.73 years, SD = 0.43; 42.09% girls) from 16 classes (M = 54.94, SD = 2.64) was tracked across three waves of surveys with 1-year intervals. The results revealed that adolescents did not select friends based on similarities in aggression or victimization, yet interactions with friends influenced individuals' levels of aggression or victimization. Popularity norms for aggression were negative in all classes, and both friendship selection and influence effects related to aggression were non-significant in all three groups. Although certain victimization-related effects were significant in specific groups, the overall moderating role of negative popularity norms was not significant. Descriptive norms for aggression did not moderate any of these processes. These findings help understand the dynamics relationship of aggression (and victimization) and friendship networks among Chinese middle adolescents, highlighting the potential role of establishing negative aggression popularity norms as potential strategies to curb the spread of aggression.